Analisis Peranan Subsektor Tanaman Pangan terhadap Perekonomian Jawa Barat - Wilaga Azman Haris; Ma’mun Sarma; A. Faroby Falatehan (P4W LPPM IPB, 2017)
Agriculture sector plays important role in regional development. Agriculture sector’s role involves other sectors such as input provider, feed provider, Gross Domestic Product provider, labor provider, and household income main source. One of agriculture subsector is food crop whereas paddy, corn, and soybean are food crop commodities that have important and stategic roles in development. Their production are targeted to achieve self sufficiency by 2017. The main objective of this research was to analyze the role of food crop subsector to West Java’s economy. The specific objective of this research involve output structure analysis, gross added value structure analysis, linkage analysis, and final demand impact analysis. This research employs secondary data. Secondary data used West Java Input-Output Table 2010. Secondary data analysis applies input output anaylisis to answer objective of this research among output structure analysis, gross added value structure analysis, linkage analysis, final demand impact analysis. The results showed that the food crop’s output structure and gross value added structure tends to low. Food crop also does not show strong linkage with its upstream sectors and downstream sectors. Final demand impact to output, gross added value, and household income also show that the food sector is low even though the food crop has better ability to absorb labor than of processing industry sector.